2D CdO‐Based Heterostructure as a Promising Visible Light Water‐Splitting Photocatalyst. Issue 8 (13th March 2020) - Wang, Guangzhao; Zhi, Yan; Xia, Liangping; Chang, Junli; Yuan, Binfang; Guo, Xiaogang; Li, Yadong; Xiao, Shuyuan; Yuan, Hongkuan
Abstract : A 2D CdO/g‐C3 N4 heterostructure (CdCHT) is designed as a potential photocatalyst. Using first‐principle calculations, it is found that CdCHT is a type‐II heterostructure, which promotes the separation of photoinduced carriers and thereby facilitates water reduction and oxidation at different layers. Visible light‐absorption ability is obviously improved compared with the constituent single layers. Especially, the band edge alignments of CdCHTs with biaxial strains satisfy water redox energy levels within the pH range between 4.3 and 12.3, which ensures the occurrence of the water redox reaction. Furthermore, the calculation of free energy proves the high hydrogen production activity of CdCHT. These factors render CdCHT to be suitable for water‐splitting photocatalysis. Abstract : Type‐II band alignments of CdO/g‐C3 N4 heterostructures (CdCHTs) facilitate water reduction and oxidation at different layers. Visible light‐absorption ability is obviously improved compared with the constituent single layers. Especially, band edge positions satisfy water redox energy levels within the pH range between 4.3 and 12.3. These factors render CdCHTs to be promising water‐splitting photocatalysts.